Hubungan Hubungan Antara Pengetahuan Dengan Upaya Pencegahan Anemia Pada Ibu Hamil - Saputri, Intan Arum (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2023)
According to the World Health Organization (WHO), the prevalence of the maternal mortality rate (MMR) is around 303,000 live births. The prevalence of AKI in Indonesia has decreased from 2018-2019 with a total of 4,226 to 4,221 per 100,000 live births, the cause of AKI is bleeding around 1,280 per 100,000 live births. Based on WHO data in 2017 the infant mortality rate was around 29 per 1,000 live births, based on the results of the Ministry of Health in 2017 the prevalence of IMR was 24 per 1,000 live births, based on data according to WHO the prevalence of anemia was around 41.8% of pregnant women experiencing anemia, while in Indonesia who experienced anemia in pregnant women in 2013 37.2% of pregnant women experienced low anemia, in 2018 there was an increase in anemia of pregnant women 48.9% of pregnant women experienced high anemia, based on the results of the government in 2019 the minimum prevalence rate decreased by about 28 %. The purpose of this study was to determine the relationship between knowledge and efforts to prevent anemia in pregnant women. This type of research is a literature review with a systematic review method. The population of this study were pregnant women and a minimum sample of 30 respondents. The source of literature in this study comes from Google Scholar. The results of the literature study that have been carried out have obtained 5 articles, where articles that discuss the relationship between knowledge and efforts to prevent anemia in pregnant women from 5 articles state that there is a relationship between knowledge and efforts to prevent anemia in pregnant women, The conclusion is that there is knowledge with efforts to prevent anemia in pregnant women. It is hoped that pregnant women who have anemia can increase their knowledge and pregnant women are expected to always check their pregnancy regularly and can make efforts to prevent anemia in pregnant women. Reading materials : 12 books, 5 articles (2011-2021) Keywords: knowledge, attitude, prevention of anemia, pregnant women